(untitled) (Sociologisk Forskning, 2017)
Based on research in Swedish multi-ethnic areas, this paper examines discourses of unrest among youth in multi-ethnic, tower-block suburbs. While there is a focus on the mechanisms of racialized social exclusion among the youth, the preoccupation among local actors including social workers, police, principals and representatives of NGOs as is with the ‘area of exclusion’ itself as causing the problems of urban unrest. Such problematizing highlights broader policy changes in Sweden, where the main responsibility for welfare is put on the individual, rather than on the collective and the state.